Performance of Clinical Nurse Educators in Teaching Pharmacology and Medication Management: Nursing Students' Perceptions - Ghamari Zare; Adib-Hajbaghery (Kashan University of Medical Sciences, 2016)
Background Pharmacological knowledge and medication management skills of student nurses greatly depend on the clinical nurse educators' performance in this critical issue. However, the Iranian nurse educators' performance in teaching pharmacology and medication management are not adequately studied. Objectives The current study aimed to investigate the nursing students' perceptions on the status of clinical pharmaceutical and medication management education. Materials and Methods A cross-sectional study was conducted on all 152 nursing students registered in the seventh and eighth semesters at the Qom and Naragh branches of Islamic Azad University, and Kashan University of Medical Sciences in 2013 - 2014 academic year. The students' perceptions on the performance of clinical nurse educators in teaching pharmacology and medication management were assessed using a researcher made questionnaire. The questionnaire consisted of 31 items regarding clinical educators' performance in teaching pharmacology and medication management and two questions about students' satisfaction with their level of knowledge and skills in pharmacology and medication management. Descriptive statistics was employed and analysis of variance was performed to compare the mean of scores of teaching pharmacology and medication management in the three universities. Results Among a total of 152 subjects, 82.9% were female and their mean age was 22.57 ± 1.55 years. According to the students, instructors had the weakest performance in the three items of teaching pharmacology and medication management based on the students' learning needs, teaching medication management through a patient-centered method and teaching pharmacology and medication management based on the course plan. The students' satisfaction regarding their own knowledge and skill of pharmacology and medication management was at medium level. Conclusions Nursing students gave a relatively low score in several aspects of their instructors' performance regarding teaching pharmacology and medication management. It seems that many clinical nurse educators in the studied settings were incompetent especially in teaching pharmacology and medication management, while these are critical areas and need special attention.